1997
DOI: 10.1063/1.872200
|View full text |Cite
|
Sign up to set email alerts
|

Rayleigh–Taylor instability of steady ablation fronts: The discontinuity model revisited

Abstract: A new model for the instability of a steady ablation front based on the sharp boundary approximation is presented. It is shown that a self-consistent dispersion relation can be found in terms of the density jump across the front. This is an unknown parameter that depends on the structure of the front and its determination requires the prescription of a characteristic length inherent to the instability process. With an adequate choice of such a length, the model yields results, in excellent agreement with the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
183
0
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 135 publications
(193 citation statements)
references
References 31 publications
7
183
0
2
Order By: Relevance
“…Another stabilization mechanism in ablative RMI, called dynamic overpressure, is discussed in Goncharov (1999) and Goncharov et al (2000), in which the sharp-boundary model (SBM) was used instead of the deflagration model. The SBM was originally developed to study ablative RTI (Piriz et al 1997). It was shown that, using the isothermal approximation of the ablation front, the SBM reproduces the results of the self-consistent RTI theory (Sanz 1994(Sanz , 1996.…”
Section: (E) Rm-like Instabilities and Ablative Rmimentioning
confidence: 99%
See 1 more Smart Citation
“…Another stabilization mechanism in ablative RMI, called dynamic overpressure, is discussed in Goncharov (1999) and Goncharov et al (2000), in which the sharp-boundary model (SBM) was used instead of the deflagration model. The SBM was originally developed to study ablative RTI (Piriz et al 1997). It was shown that, using the isothermal approximation of the ablation front, the SBM reproduces the results of the self-consistent RTI theory (Sanz 1994(Sanz , 1996.…”
Section: (E) Rm-like Instabilities and Ablative Rmimentioning
confidence: 99%
“…It is also an important phenomenon in inertial confinement fusion (ICF), as it invariably develops during the early stages of target irradiation, when a sequence of shocks travels through the target. As the shock fronts are not uniform, their corrugations will induce a highly perturbed flow behind them, which will be the seed for the Rayleigh-Taylor instability (RTI) that occurs later during the acceleration phase of the target (Ishizaki & Nishihara 1997;Piriz et al 1997;Nishihara et al 1998;Goncharov 1999;Velikovich et al 2000). The RMI has also been thoroughly studied in experiments designed in shock tubes (Jones & Jacobs 1997;Zabusky 1999;Brouillette 2002) and has also become a fascinating research topic in the field of high-energy density experiments in matter.…”
Section: Introductionmentioning
confidence: 99%
“…[35][36][37] In conventional ICF, the laserdriven target compression and heating require a high degree of irradiation symmetry so as to limit the growth of hydrodynamical instabilities. 38,39 In order to fulfill drastic symmetry requirements, ICF facilities under construction such as the National Ignition Facility 40 or the Laser Megajoule 41 rely on the so-called indirect drive approach wherein nanosecond laser pulses first hit the inner walls of a high-Z hohlraum containing the DT pellet. The laser-hohlraum interaction then produces a quasihomogeneous x-ray radiation bath, which, by tailoring the incident laser intensity profile, drives a series of shock waves expected, if efficiently synchronized, to both compress and heat the target up to ignition temperatures.…”
Section: B Fast Ignition Scenariomentioning
confidence: 99%
“…Nevertheless, the problem is not mathematically closed. A possible option is to keep one free parameter that can be taken a posteriori as an input from 1D simulations [8]. In the present model, the existence of two ablation fronts leads to keep two free parameters: r D , the ratio between the plateau and the peak density and d p , the plateau length.…”
Section: Analytical Discontinuity Model For Stability Analysismentioning
confidence: 99%